Monoterpene derivatives from the flowers of the Hemerocallis minor Mill. (September 2017) - Zhao, Xincai; Guo, Yigong; Zhang, Yu; Xie, Yangguo; Yan, Shikai; Jin, Huizi; Zhang, Weidong
Graphical abstract: Highlights: Seventeen compounds, including three new monoterpene derivatives, named hemerolides A–C (1 –3 ), and one new phenol derivative hemeratrol A (4 ) were isolated from the flowers of Hemerocallis minor Mill. Their structures and absolute configuration were determined by NMR analyses and CD data. The isolated compounds were evaluated for their inhibitory activity against NF-κB activation. Abstract: Three new monoterpene derivatives, named hemerolides A–C (1 –3 ), one new phenol derivative hemeratrol A (4 ), along with thirteen known compounds (5 –17 ) were isolated from the flowers of Hemerocallis minor Mill. The structures of the isolated compounds were determined by a combination of 1D and 2D NMR, HRESIMS, and CD spectroscopic data. All the isolates were evaluated their inhibitory activity against NF- κB activation in HeLa cells. Among them, compound4 displayed a moderate inhibition of NF- κB activation with IC50 value of 41.7 μM.